2014
DOI: 10.4269/ajtmh.14-0147
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the UCLA Department of Medicine Malawi Global Health Clinical Elective: Lessons from the First Five Years

Abstract: Abstract. In 2008, the UCLA Department of Medicine established a three-week clinical elective in Malawi, Africa, for Medicine and Medicine/Pediatrics residents. We sought to determine whether the elective resulted in improved medical knowledge, alterations in career trajectory, and whether the opportunity for the elective influenced selection of UCLA for residency. A 29-question survey was distributed to all graduates of the elective from 2009-2013. Surveys were distributed to 40 individuals, with 33 responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 6 publications
3
25
0
Order By: Relevance
“…We found that applicants with an interest in GHE were more likely to be aware of CCHMC's GHE curriculum, and GHE was a more significant factor for them when ranking a program. This finding is consistent with a number of studies from other subspecialties (Bazemore et al, 2007;Dey et al, 2002;MonroeWise et al, 2014;Shull et al, 2014), however, to our knowledge, this is the first report from a large pediatric residency program. To keep pace with this interest among residents, pediatric residency programs have increasingly tried to develop, offer, and publicized their GHE activities (Castillo, Castillo, & Dewitt, 2011).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…We found that applicants with an interest in GHE were more likely to be aware of CCHMC's GHE curriculum, and GHE was a more significant factor for them when ranking a program. This finding is consistent with a number of studies from other subspecialties (Bazemore et al, 2007;Dey et al, 2002;MonroeWise et al, 2014;Shull et al, 2014), however, to our knowledge, this is the first report from a large pediatric residency program. To keep pace with this interest among residents, pediatric residency programs have increasingly tried to develop, offer, and publicized their GHE activities (Castillo, Castillo, & Dewitt, 2011).…”
Section: Discussionsupporting
confidence: 79%
“…In addition we document that mentorship and financial support are components perceived as important to pediatric residents interested in GHE participation. We hope that our findings help inform residency program directors and faculty across the USA who are looking to design a GHE program and potentially enhancing resident recruitment (Shull et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the presence of an IHE in undergraduate and postgraduate medical education has been well-documented as an effective recruitment tool for the medical school or residency program in question. 1,12,25 It is possible, therefore, that recruiting postgraduates who participate in IHEs may increase local service to underserved populations in that area. The healthcare system, academy, and community may therefore benefit as a result, regardless of whether IHEs instill a new social responsibility into their participants, or merely recruit such practitioners to their region.…”
Section: Discussionmentioning
confidence: 99%
“…However, multiple studies demonstrate the positive impact of IHEs on medical learners’ intention to care for domestic underserved populations. 11 , 12 For example, among US medical students who had participated in a 2-year international health fellowship, 80% (35/44) reported an intention to practice “primarily in the United States and from time to time overseas.” 13 Greysen found that among their 229 respondents who identified having had any global health (GH) experience during or after their training, 73% indicated that <10% of their total professional time was dedicated to international health work in the past year. 3 …”
Section: Introductionmentioning
confidence: 99%